Reformulation of Mu'tazilah Theology and the Birth of al-Ash'ariyah Theology as Moderate Islamic Understanding - Fahrul Rozi; Mutohharun Jinan; Iyas Ali Nurani; Aboubacar Barry (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The turmoil between Mu'tazilah and al-Ash'ari refers to a significant difference in the views of Kalam. The theological reformulation from Mu'tazilah to al-Ash'ari carried out by Abu Hasan al-Ash'ari combined the textualist methods of the Salaf with the rationalist Mu'tazilah, known as the moderate Islamic school. This research focuses on the conflict and values ​​that were reformulated based on the history and shifts in thought between Mu'tazilah and al-Ash'ari. Therefore, this study aims to provide an overview of the initial values ​​of Mu'tazilah thought and the shifts that occurred after al-Ash`ari reformulated the thought. This study uses a qualitative research method by looking at various written sources. So, the reference source for this study is the literature. Data collection techniques through documentation were then analyzed using the descriptive analysis method. The interpretation method is used to analyze the data. This aims to interpret the object of understanding according to the way the researcher understands it. The results of this study explain the reformulation of Mu'tazilah ideas to al-Ash`ari related to the main points of God's Recognition, human free will, and God's justice, as well as the role of reason and revelation, which are too dominant in the use of rationality. In Indonesia, this reformulation is known as Moderate Islam with various practices internalized in Indonesian culture, such as a friendly attitude towards others, maintaining peace, and the ability to accept and handle differences.